PENGARUH FAKTOR YANG EFEKTIF TERHADAP AUDIT DELAY: Studi Empiris Pada Perusahaan yang Listing di BEI Periode 2008-2012 - Fuad, Khoirul (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2013)
This study aims to examine the factors that affect audit delay. The influencingfactors are the following, firm size, the percentage change of earnings per share, industry,extraordinary goods, audit opinion, debt ratio, KAP size, profit or loss operation andprofitability level. The sampling method used is purposive sampling with the followingcriteria such as The Company is listed on the Indonesia Stock Exchange (IDX) in 2008- 2012. The Company has issued annual financial statements for the period 2008-2012.The financial statements are presented in rupiah. The sample has a financialreporting period based on the calendar year ending 31 December. Issued auditedfinancial statements during 2008, 2009, 2010, 2011, 2012 respectively. There are 531companies listed on the BEI during 2008-2012. Based on the criteria of this studyobtained 240 companies used as research samples. The analysis technique used to analyzethe hypothesis of this research is logistic regression analysis. The results of this studyindicate that operating profit or loss has a positive effect on audit delay. The percentagechange in earnings per share and Auditor Opinion negatively impacted the audit delay.The size of the firm, the industry, the extraordinary goods, the size of KAP, the debt ratioand the level of profitability have no effect on audit delay.